A comparative analysis of the role of water in the binding pockets of ionotropic glutamate receptors. - Vijayan, R; Sahai, M; Czajkowski, T; Biggin, P (2010)
The binding pockets within proteins often contain water molecules. The ligand-binding core of ionotropic glutamate receptors represents an example where the binding pocket has many crystallographically reported waters, but the precise role remains unclear. It is also unclear to what extent the dynamic properties of these waters are conserved across the different receptor subtypes. In order to shed some light on these aspects we have performed multiple molecular dynamics simulations of the ligand binding core of four glutamate bound iGluR structures (GluA2, GluK1, GluK2, and GluN2A) and one apo structure (GluA2). We find that the water positions are reproduced from the simulations, but they also reveal that all but one water molecule in the binding site can be rearranged or replaced with water molecules from the bulk that enter the binding site through transient water channels. This one exception is not reported in the apo crystal structure but within 15 ns of simulation, a water molecule enters the site from the bulk suggesting that it is a favoured position regardless of the state of the protein. Further calculations demonstrate that whilst it is not needed in order to be able to predict the correct binding pose, it does contribute a large favourable interaction energy. We also find that one conserved water has a much stronger interaction with the protein in GluA2, GluK1 and GluK2 compared to the GluN2A receptor. The position of this water molecule is such that it can influence the dynamics of the proposed switch in the GluA2 and GluK1/2 receptors.